2016
DOI: 10.2147/ndt.s105199
|View full text |Cite
|
Sign up to set email alerts
|

A family-oriented therapy program for youths with substance abuse: long-term outcomes related to relapse and academic or social status

Abstract: ObjectiveThe abuse of illegal substances by youths in Taiwan has become a major public health issue. This study explores the outcomes (relapse rate and academic or social status) of a family-oriented therapy program conducted for substance-using youths who were referred by a judge to participate in it.MethodsThe present study includes 121 participants categorized into three groups: 36 youths underwent a weekly ten-session outpatient motivational enhancement psychotherapy (MEP) group program; 41 youths particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In this study, the respective program consists of 10 weekly psychotherapy sessions based on motivational enhancement principles [28], as well as 10 weekly parental skill training sessions [29, 30] for the youths’ caregivers. The details of this family-oriented treatment program and its effectiveness on youths with substance abuse issues and their caregivers have been provided in previous studies [31, 32]. The adolescents who have completed the family-orientated treatment program also received long-term follow-up in the justice system, which offers us a great opportunity to determine the relapse risk between ketamine users and those who use stimulants (methamphetamine or MDMA).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the respective program consists of 10 weekly psychotherapy sessions based on motivational enhancement principles [28], as well as 10 weekly parental skill training sessions [29, 30] for the youths’ caregivers. The details of this family-oriented treatment program and its effectiveness on youths with substance abuse issues and their caregivers have been provided in previous studies [31, 32]. The adolescents who have completed the family-orientated treatment program also received long-term follow-up in the justice system, which offers us a great opportunity to determine the relapse risk between ketamine users and those who use stimulants (methamphetamine or MDMA).…”
Section: Introductionmentioning
confidence: 99%
“…A study of adolescent crack users revealed high rates of relapse of 65.9 and 86.4% in the first and third months, respectively [32]. Our previous cohort revealed that the 2-year relapse rate reached 33.1% among substance-use adolescents [17]. This finding suggests that breaking the drug addiction cycle for substance-using adolescents remains a challenge [33].…”
Section: Discussionmentioning
confidence: 88%
“…Before taking part in this research, each participant submitted a signed written informed consent, while the researchers emphasized whether to take part in this research or not would never affect his or her legal status and that all personal information provided would be kept strictly confidential. Details of treatment protocols and research procedures have been demonstrated elsewhere [16,17].…”
Section: Research Participantsmentioning
confidence: 99%
See 2 more Smart Citations